Uposażenie parafii obrzańskiej i wybrane aspekty działalności duszpasterskiej w okresie pocysterskim w latach 1836-1861 - Zając, Paweł (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
After 1836 the income of the parish priest and the parish were to be guaranteed by the Prussian administration, but the full amount was not paid for several years. The original project of opening a home for retired priests was never realized. The parish priest was assisted in his pastoral ministry by Fr. Piotr Widawski, who actually fulfilled the responsibilities of the curate. Charitable work was continued, especially the support of the widows who lived in the parish hospital, but eventually the Prussian authorities ordered for it to be shut down. Patriotic activity was also pursued and parish branches of the Polish League (Liga Polska) were founded. A short stay of the Jesuits was marked by an untimely death of Fr. Karol Antoniewicz, who was buried in the crypt of the church in Obra.